2013
DOI: 10.1002/2013jd020258
|View full text |Cite
|
Sign up to set email alerts
|

Detection of carbon monoxide trends in the presence of interannual variability

Abstract: [1] Trends in fossil fuel emissions are a major driver of changes in atmospheric CO, but detection of trends in CO from anthropogenic sources is complicated by the presence of large interannual variability (IAV) in biomass burning. We use a multiyear model simulation of CO with year-specific biomass burning to predict the number of years needed to detect the impact of changes in Asian anthropogenic emissions on downwind regions. Our study includes two cases for changing anthropogenic emissions: a stepwise chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 96 publications
1
17
0
Order By: Relevance
“…CO emissions inventories still present large uncertainties (Streets et al, 2013), and separating anthropogenic and biomass burning contributions is essential for attributing CO long-term trends (Strode and Pawson, 2013).…”
Section: George Et Al: Long-term Co Records From Mopitt and Iasimentioning
confidence: 99%
“…CO emissions inventories still present large uncertainties (Streets et al, 2013), and separating anthropogenic and biomass burning contributions is essential for attributing CO long-term trends (Strode and Pawson, 2013).…”
Section: George Et Al: Long-term Co Records From Mopitt and Iasimentioning
confidence: 99%
“…Satellite observations show 51 increasing trends in several tropospheric Asian trace gases over the last decade, e.g. ozone at 52 ~1-3 % year -1 (Verstraeten et al, 2015), CO at 3% year -1 (Strode and Pawson, 2013), NO x at 53 ~3.8 -7.3 % year -1 (Schneider and van der A, 2012; Ghude et al, 2013). Biomass burning is 54 another major contributor to the observed growth in these trace gases (van der Werf et al, 55 2006).…”
Section: Introduction 42mentioning
confidence: 99%
“…For 2004-2005 over North America, it was estimated that 8 % of smoke plumes reached more than 2.5 km above the boundary layer [68]; only a small number of these are lofted directly to the upper troposphere. Strode et al [28] indeed found that the influence on tropospheric CO due to biomass burning decreases with height, being smaller at 500 hPa than at the surface.…”
Section: Effects On Ut/ls Compositionmentioning
confidence: 96%
“…This effect, they claim, could become more severe in the future, as boreal forest regions become hotter and drier. Without examining ENSO influences, Strode et al [28] discuss how biomass burning strongly impacts the interannual variability of CO in northern mid-latitudes, which affects the ability to detect anthropogenically driven trends in CO.…”
Section: Gasesmentioning
confidence: 99%